Transient gamma-secretase inhibition accelerates and enhances fracture repair likely via Notch signaling modulation - Wang, Cuicui (Bone, 2014)
Approximately 10% of skeletal fractures result in healing complications and non-union, while most fractures repair with appropriate stabilization and without pharmacologic intervention. It is the latter injuries that cannot be underestimated as the expenses associated with their treatment and subsequent lost productivity are predicted to increase to over $74 billion by 2015. During fracture repair, local mesenchymal stem/progenitor cells (MSCs) differentiate to form new cartilage and bone, reminiscent of events during skeletal development. We previously demonstrated that permanent loss of gamma-secretase activity and Notch signaling accelerates bone and cartilage formation from MSC progenitors during skeletal development, leading to pathologic acquisition of bone and depletion of bone marrow derived MSCs. Here, we investigated whether transient and systemic gamma-secretase and Notch inhibition is capable of accelerating and enhancing fracture repair by promoting controlled MSC differentiation near the fracture site. Our radiographic, microCT, histological, cell and molecular analyses reveal that single and intermittent gamma-secretase inhibitor (GSI) treatments significantly enhance cartilage and bone callus formation via the promotion of MSC differentiation, resulting in only a moderate reduction of local MSCs. Biomechanical testing further demonstrates that GSI treated fractures exhibit superior strength earlier in the healing process, with single dose GSI treated fractures exhibiting bone strength approaching that of un-fractured tibiae. These data further establish that transient inhibition of gamma-secretase activity and Notch signaling temporarily increases osteoclastogenesis and accelerates bone remodeling, which coupled with the effects on MSCs likely explains the accelerated and enhanced fracture repair. Therefore, we propose that the Notch pathway serves as an important therapeutic target during skeletal fracture repair.